2010
DOI: 10.1177/0961203309360540
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid-inducible gene-I (RIG-I) is induced by IFN-γ in human mesangial cells in culture: possible involvement of RIG-I in the inflammation in lupus nephritis

Abstract: Interferon-gamma is a potent Th1-type cytokine and a key molecule in the pathogenesis of autoimmune diseases including lupus nephritis. Retinoic acid-inducible gene-I is a putative RNA helicase that plays an important role in immune and inflammatory reactions. We previously demonstrated the increased expression of the retinoic acid-inducible gene-I protein in the kidney tissue of patients with lupus nephritis, and the presence of a significant amount of retinoic acid-inducible gene-I mRNA in the urinary sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…As mentioned above (28,29), Rig-I itself was an authentic ISG, and its mRNA level in normal myeloid cells was significantly elevated by either IFN-α or IFN-γ stimulation ( Fig. 2 B and C).…”
Section: Rig-i Induction Functionally Contributes To Ifn Plus Atra-inmentioning
confidence: 91%
See 2 more Smart Citations
“…As mentioned above (28,29), Rig-I itself was an authentic ISG, and its mRNA level in normal myeloid cells was significantly elevated by either IFN-α or IFN-γ stimulation ( Fig. 2 B and C).…”
Section: Rig-i Induction Functionally Contributes To Ifn Plus Atra-inmentioning
confidence: 91%
“…Nevertheless, because RIG-I expression itself is highly inducible by IFN or RA signaling (Fig. S2 B and C) (21,28,29), we argue that RIG-I might also possess a relatively independent regulatory role on the ensuing IFN intracellular signaling process. In line with this assumption, we have previously demonstrated an important physiological role of RIG-I in negatively regulating myelopoiesis, partly through maintaining the myeloid expression of a classic ISG, Icsbp (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, IFN-did not induce the expression of IFN-, which is known to be a target gene of IRF-7, in mesangial cells (Fig. 3) (Imaizumi et al, 2010) Interestingly, pretreatment of cells with dexamethasone inhibited the IFN--induced expression of monocyte chemoattractant protein (MCP)-1 mRNA but did not affect the induction of RIG-I or IRF7 mRNA in mesangial cells. The induction of MCP-1 mRNA by IFN-was not inhibited by the knockdown of NF-κB p65, indicating that the NF-κB signaling pathway was not involved.…”
Section: The Retinoic Acid-inducible Gene-i (Rig-i) and Lupus Nephritismentioning
confidence: 83%
“…3. (Imaizumi et al, Lupus 2010) In a recent study, we showed that RIG-I controlled the immune and inflammatory responses by regulating the expression of various downstream genes, including IFNs regulatory factor (IRF) genes, in mesangial cells (Imaizumi et al, 2010). We previously found RIG-I was highly expressed in the glomeruli examined in biopsy specimens from patients with lupus nephritis, and the level of expression correlated with the severity of acute inflammatory lesions (Suzuki et al, 2007).…”
Section: The Retinoic Acid-inducible Gene-i (Rig-i) and Lupus Nephritismentioning
confidence: 99%